PERAN TENAGA PENDIDIK DALAM PEMBELAJARAN JARAK JAUH DI ERA COVID-19 - Dede Gunandi; Muhammad Khairunnas; Zulmuqim Zulmuqim; Demina Demina (Kelola: Journal of Islamic Education Management, 2021)
Distance learning became a trend in the era of the emergence of the Covid-19 pandemic. Distance learning or often known as PJJ is learning done without face-to-face between students and educators. Distance learning  does  not  exist  in  the Indonesian education curriculum before that. This system suddenly happened because of the closure of direct learning or face-to-face learning from PAUD to Universities as a form  of anticipation of Covid-19 transmission. The practice, the implementation of learning on the long distance will use daring/online or daring/online methods. pjj will make more use of Technology Information in conducting learning. Therefore,   this   paper   will   help   educators   in developing plans and methods that can be used during the distance learning process.